If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -5 = -8(6 + 5n) Reorder the terms: -5 + 3y = -8(6 + 5n) -5 + 3y = (6 * -8 + 5n * -8) -5 + 3y = (-48 + -40n) Solving -5 + 3y = -48 + -40n Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3y = -48 + 5 + -40n Combine like terms: -5 + 5 = 0 0 + 3y = -48 + 5 + -40n 3y = -48 + 5 + -40n Combine like terms: -48 + 5 = -43 3y = -43 + -40n Divide each side by '3'. y = -14.33333333 + -13.33333333n Simplifying y = -14.33333333 + -13.33333333n
| 100=y^2+2y-96 | | y-8=-2(x-(-3)) | | x-5=1.19 | | -q^2+2q-1=0 | | -13=5m+20m-2m | | -2=x^2-5x+2 | | X(.10)+x=1375 | | 11w-3(2-6w)=81 | | 1+5d=11 | | 4w^2+6w-7=0 | | 2x+6=21-3 | | 2x-x+5x-9= | | 0.6a+5-0.3a-7= | | 2y-3.5=6.5 | | 5z=2.9+3.6 | | m^2+3m-3=0 | | 0=y^2+2y-96 | | 5=5-5t | | 3x-21=5x-5 | | -4x+-4-9=-12x+11 | | 35=8-9y | | -p^2-2p=0 | | 2(j-7)=64 | | 3y-8=9 | | 2x+4(x+3)=36 | | 4e^3x+6=30 | | -3x-3x=26-2 | | 8c-13=3c+36 | | 2u^2-3u=0 | | -9=k-5k+7 | | 4x^2-15=25 | | 6t+17-3t=38 |